EXPLORING NOSQL DATABASES IN MEDICAL IMAGE MANAGEMENT - Timmana Hari Krishna, Dr C. Rajabhushanam, Dr C. Rajabhushanam (International Journal of Modern Agriculture, 2020)
Medical Imaging technology is a revolution in Health care industry over the past 3 decades. It allows doctors to notice disease prior and progress patient outcomes. It produces huge semi-structured and unstructured image data as health records which does not contain any fixed schema. It entails better data model for storage and retrieval. NoSQL (Not only SQL) databases are considerably suitable to store and retrieve the Big Data. Hence proposing NOSQL database to store Medical health records. This paper intends to compare the different NOSQL databases in the view of imaging technology